Identity as Discourse: 'The Person in Need of Guardianship'. (24th June 2020) - Barel, Michal; Doron, Israel (Issi); Strier, Roni
Abstract: This article presents a critical discussion of the legal institution of adult guardianship in Israel. Based on a critical discourse analysis' study of official guardianship reports for older adults submitted by social workers to family courts in Israel, findings reveal how guardianship institutional procedures construct the personal life stories of older persons into legalistic guardianship paradigm, and in doing so they create a new identity of 'a person in need of guardianship'. The article further delineates how 'a person in need of guardianship' (as well as a 'guardian') is a discursive identity, a subject who never existed prior to the guardianship proceeding, a legal creation which does not reflect the complexities and realities of older persons.